Scalarane sesterterpenes from the Egyptian Red Sea sponge Phyllospongia lamellosa. Issue 4 (28th January 2015) - Hassan, Marwa H.A.; Rateb, Mostafa E.; Hetta, Mona; Abdelaziz, Tarek A.; Sleim, Mohamed A.; Jaspars, Marcel; Mohammed, Rabab
Abstract: Biology and HRESIMS-guided screening of the dichloromethane fraction of the marine sponge Phyllospongia lamellosa collected from the Red Sea resulted in the isolation and characterization of five new scalarane sesterterpenes; phyllospongins A–E (1 –5 ), in addition to four known derivatives, 12α-acetoxy-20, 24-dimethyl-25-norscalar-16-en-24-one (6 ), 12α-acetoxy-13β, 18β-cyclobutan-20, 24-dimethyl-24-oxoscalar-16-en-25β-ol (7 ), 12α-acetoxy-24, 25-epoxy-24-hydroxy-20, 24-dimethylscalarane (8 ), and scalardysin-A (9 ) that were previously isolated from Carteriospongia sp. and Dysidea sp. The structures of the isolated compounds were fully characterized using NMR spectroscopic techniques and mass spectrometric analysis. All the isolated compounds were tested for their cytotoxic activity against human cancer cell lines (HePG-2, MCF-7, and HCT-116) and antibacterial activity against some Gram-positive and Gram-negative strains. Graphical abstract: